Development of a finite element enriched method adapted for the case of multiple cracked structure - Durif, Emilien; Réthoré, Julien; Combescure, Alain (European Journal of Computational Mechanics, 2010)
The present method is based on the eXtended Finite Element Method and the partition of unity properties which allows the addition of enriched functions in the displacement field discretization. Those correspond to the analytical displacement field near a straight crack. The additionnal degrees of freedom correspond directly to the Stress Intensity Factors. This method is validated in mode 1 and mixed mode. A parametric study has been performed to analyse the effect of different parameters on the accuracy of the method. The case of two shading cracks has also been investigated.